Teatro michoacano de finales del siglo XX. Aportaciones del dramaturgo José Manuel Álvarez - Vega Gómez, Luis Copérnico (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
The actor, director and playwright José Manuel Álvarez, a native of Santa Clara del Cobre, was a fundamental piece of Michoacán theater in the decades from the sixties to the eighties of the last century, by maintaining a constant theatrical activity and founding the extinct State Theater Company, which allowed him to be a recognized figure in the country. However, the fact of having stayed in Michoacán and having developed most of his dramatic work in the province prevented him from gaining the recognition achieved by some of his contemporaries who moved to Mexico City. Although Michoacán has an active and diverse theater scene, Álvarez's dramaturgy is unknown to the new generations and remains forgotten by his contemporaries. Few people know his dramatic texts, which were a watershed on the state scene. This project aims to show the contributions of the Michoacán playwright José Manuel Álvarez (1931-1998) to the local theater, through the compilation and synthesis of his dramatic work, as well as the critical edition of his unpublished work Tres hombres de confianza (‘Three trustable men’), to place it in the context of dramaturgy in Michoacan.

El actor, director y dramaturgo José Manuel Álvarez, oriundo de Santa Clara del Cobre, fue pieza fundamental del teatro michoacano en las décadas de los años sesenta a ochenta del siglo pasado, al mantener una constante actividad teatral y fundar la extinta Compañía Estatal de Teatro, lo que le permitió ser una figura reconocida en el país; sin embargo, el hecho de haber permanecido en Michoacán y haber desarrollado la mayor parte de su trabajo dramático en provincia evitó que este tuviera el reconocimiento que lograron algunos de sus contemporáneos que se mudaron a la Ciudad de México. Si bien Michoacán tiene una escena teatral activa y diversa, la dramaturgia de Álvarez es desconocida por las nuevas generaciones, y permanece olvidada para sus contemporáneos. Pocas personas conocen sus textos dramáticos, que fueron un parteaguas en la escena estatal. Este proyecto pretende mostrar las aportaciones del dramaturgo michoacano José Manuel Álvarez (1931-1998) al teatro local, mediante la recopilación y síntesis de su obra dramática, así como la edición crítica de su obra inédita Tres hombres de confianza, para situarla en el contexto de la dramaturgia michoacana.
Facultad de Letras. Maestría en Estudios del Discurso
Keywords: info:eu-repo/classification/cti/4; FL-M-2023-0316; Dramaturgia; Recopilación; Teatro michoacano; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16453